(untitled) (Baghdad Science Journal, 2021)
Abstract The experiment has been carried out in the Syrian National Commission of Biotechnology, during the growing season 2018/2019, to study the effect of abiotic stresses (salinity and osmotic stresses) on the activity of some antioxidant enzymes and biochemical traits in Catharanthus roseus. The experiment has been laid according to (CRD) with three replications. The seeds have been sterilized by NaOCl solution (0.5% v/v), then planted on MS medium. Plantlets have been moved to MS medium enriched with NAA (1 mg.L-1) and BA (2 mg.L-1). The callus has been initiated from leaves using MS medium containing NAA (1 mg L-1) and KIN (2 mg.L-1). After 60 days, callus has been transferred to MS medium supplemented with different concentrations of PEG 6000 (-0.2, -0.3, -0.4, -0.5 MPa), and NaCl (25, 50, 75, 100 mM) in succession as stimulating agents. The results show that the top value of solutes leakage has been in the salt and osmotic treatments (28.04 and 26.98% respectively) compared with the control (8.563%). MDA content has significantly been higher in salt stress (102.3 µmol.g-1 FW) followed by the osmotic stress treatment (79.41 µmol.g-1 FW), while it was significantly lower in the non-stressed treatment (37.76 µmol.g-1 FW). An increase in the proline content occurred in both the stress treatments (4.623, 4.243 mmol.g-1 FW, respectively) compared with the control (2.477 mmol.g-1 FW). The activity of antioxidant enzymes (CAT, APX, and SOD) have significantly been higher in salt stress treatment (506.9, 12270.02 mol.min-1.mg-1 protein, 191.4 U.mg-1 protein respectively), followed by osmotic stress (259.4, 7106.22 mol.min-1.mg-1 protein, 65.60 U.mg-1 protein, respectively), while it has been significantly lower in control (126.9, 1800.38 mol.min-1.mg-1 protein, 36.03 U.mg-1 protein, respectively).